Verbal and visual stimulation effects on rectus femoris and biceps femoris muscles during isometric and concentric - Silva, Sidney B; De Abreu, Luiz Carlos; Valenti, Vitor E [UNESP]; Nogueira, Daniel V; Moraes, Éder R; Natividade, Vilma; Gallo, Paulo Rogério; Herrero, Dafne; Zacaro, Patrícia M D (Springer Nature, 2013)
Background: Coactivation may be both desirable (injury prevention) or undesirable (strength measurement). In this context, different styles of muscle strength stimulus have being investigated. In this study we evaluated the effects of verbal and visual stimulation on rectus femoris and biceps femoris muscles contraction during isometric and concentric. Methods. We investigated 13 men (age =23.1 ± 3.8 years old; body mass =75.6 ± 9.1 kg; height =1.8 ± 0.07 m). We used the isokinetic dynamometer BIODEX device and an electromyographic (EMG) system. We evaluated the maximum isometric and isokinetic knee extension and flexion at 60°/s. The following conditions were evaluated: without visual nor verbal command (control); verbal command; visual command and; verbal and visual command. In relation to the concentric contraction, the volunteers performed five reciprocal and continuous contractions at 60°/s. With respect to isometric contractions it was made three contractions of five seconds for flexion and extension in a period of one minute. Results: We found that the peak torque during isometric flexion was higher in the subjects in the VVC condition (p > 0.05). In relation to muscle coactivation, the subjects presented higher values at the control condition (p > 0.05). Conclusion: We suggest that this type of stimulus is effective for the lower limbs. © 2013 Silva et al.; licensee BioMed Central Ltd.
Keywords: Auditory stimulation; Electromyography; Knee; Muscles; Visual stimulation